2016
DOI: 10.1016/j.trf.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Learning to drive in young adults with language impairment

Abstract: HighlightsFirst study of entry into driving by young people with language impairment (LI).Individuals with LI are less likely than peers to have acquired a licence by age 24.Language and independence at 17 contribute to the prediction of holding a licence.Individuals with LI are at no greater risk of traffic violations/accidents.Individuals with LI may benefit from support during the preparation and test phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
2
4
0
1
Order By: Relevance
“…This could be explained by the fact that having language difficulties during adolescence may limit the breadth and variety of experiences in the community, thereby leading to shyness and lower self-esteem. As for the driver's license, young adults identified language challenges regarding the driving theory test, such as understanding the questions (Durkin et al, 2016). This is in line with previous research showing more difficulties in adolescents with DLD to understand compound nouns and verbs related to driving compared to their peers without DLD (Pandolfe et al, 2016).…”
Section: Predictive Role Of Language Abilitiessupporting
confidence: 85%
See 4 more Smart Citations
“…This could be explained by the fact that having language difficulties during adolescence may limit the breadth and variety of experiences in the community, thereby leading to shyness and lower self-esteem. As for the driver's license, young adults identified language challenges regarding the driving theory test, such as understanding the questions (Durkin et al, 2016). This is in line with previous research showing more difficulties in adolescents with DLD to understand compound nouns and verbs related to driving compared to their peers without DLD (Pandolfe et al, 2016).…”
Section: Predictive Role Of Language Abilitiessupporting
confidence: 85%
“…A total of 15 articles met all inclusion criteria. A careful examination of the 15 articles revealed that samples were reused to test different hypotheses and that, in total, only four independent samples were used, for a total of 1,051 participants with DLD: 84 participants in the Manchester Language Study Conti-Ramsden & Durkin, 2012;Conti-Ramsden et al, 2016Durkin et al, 2017Durkin et al, , 2016Toseeb et al, 2017;Winstanley, Durkin, et al, 2018;, 75 participants in the Ottawa Language Study (Beitchman et al, 2014;Johnson et al, 2010), 861 participants in the British Cohort Study (Law et al, 2009;Schoon et al, 2010a), and 31 participants in the Family Study of Speech and Language Disorders (Lewis et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations